Properties of Water Ice and Dust Particles in the Atmosphere of Mars During the 2018 Global Dust Storm as Inferred From the Atmospheric Chemistry Suite. Issue 11 (31st October 2020) - Luginin, M.; Fedorova, A.; Ignatiev, N.; Trokhimovskiy, A.; Shakun, A.; Grigoriev, A.; Patrakeev, A.; Montmessin, F.; Korablev, O.
Abstract: The properties of Martian aerosols are an integral part of the planetary climatology. Global dust storms (GDS) significantly alter spatial and vertical distributions of dust and water ice aerosols and their microphysical properties. We explored the 2018/Martian year 34 GDS with the Atmospheric Chemistry Suite instrument onboard the ESA‐Roscosmos Trace Gas Orbiter mission. Solar occultation observations of thermal infrared and near infrared channels in the 0.7–6 μm spectral range with >10 3 signal‐to‐noise ratio are used to constrain the vertical dependence and the temporal evolution of the particle properties of water ice and dust (effective radius, effective variance, number density, and mass loading) before the 2018 GDS and during its onset and decay phases. In most of the observations, the particle size of dust and water ice decreases with altitude. The effective radius of dust and water ice particles ranges in 0.1−3.5 μm and 0.1–5.5 μm, respectively. The largest aerosol particles (> 2.5 μm for dust and > 3.5 μm for water ice) are present below 10 km before the onset and during the GDS decay phase. During the peak of the GDS, dust reached altitudes of 85 km; the most frequently observed effective radius is 1–2 μm with 0.1–1 cm −3 number density and 0.1 effective variance. Detached layers of water ice composed of 0.1–1 μm particles are systematically observed at 50–100 km during this period. Below, at 0–50 km, we see the dust mixed with the main water ice layer comprising 1–4 μm particles. Plain Language Summary: Suspended in the air, mineral dust and water ice particles play a key role in thermal balance and circulation of the atmosphere of Mars and its climate. In that context, global dust storms are rare but powerful events that significantly alter spatial and vertical distributions of dust and water ice particles and their properties. The most recent event, which occurred in the summer of 2018, was monitored by the Atmospheric Chemistry Suite instrument onboard the ESA‐Roscosmos Trace Gas Orbiter mission. Solar occultation observations carried out in the visible and the middle infrared spectral ranges enabled monitoring of dust and water ice particles properties such as size, number of particles and their mass per unit volume, and the width of their size distribution during the evolution of the storm. Dust was lifted to 85 km, while water ice clouds were observed at even higher altitudes, up to 100 km. Key Points: Atmospheric Chemistry Suite solar occultations in the 0.7–6 μm spectral range separate microphysical properties of dust and water ice aerosols in Martian atmosphere The observed particle radius ranges from 0.1 to 3.5 μm for dust and from 0.1 to 5.5 μm for water ice clouds, with the largest particles found below 10 km Water ice clouds with 0.1–1 μm particles reached altitudes up to 100 km during the peak of the 2018 global dust storm